Protein Kinase C as Regulator of Vascular Smooth Muscle Function and Potential Target in Vascular Disorders - Ringvold, Helene C. (Adv Pharmacol, 2016)
Vascular smooth muscle (VSM) plays an important role in maintaining vascular tone. In addition to Ca(2+)-dependent myosin light chain (MLC) phosphorylation, protein kinase C (PKC) is a major regulator of VSM function. PKC is a family of conventional Ca(2+)-dependent α, β, and γ, novel Ca(2+)-independent δ, ε, θ, and η, and atypical ξ, and ι/λ isoforms. Inactive PKC is mainly cytosolic, and upon activation it undergoes phosphorylation, maturation and translocation to the surface membrane, the nucleus, endoplasmic reticulum, and other cell organelles; a process facilitated by scaffold proteins such as RACKs. Activated PKC phosphorylates different substrates including ion channels, pumps and nuclear proteins. PKC also phosphorylates CPI-17 leading to inhibition of MLC phosphatase, increased MLC phosphorylation and enhanced VSM contraction. PKC could also initiate a cascade of protein kinases leading to phosphorylation of the actin-binding proteins calponin and caldesmon, increased actin-myosin interaction and VSM contraction. Increased PKC activity has been associated with vascular disorders including ischemia-reperfusion injury, coronary artery disease, hypertension, and diabetic vasculopathy. PKC inhibitors could test the role of PKC in different systems, and could reduce PKC hyperactivity in vascular disorders. First generation PKC inhibitors such as staurosporine and chelerythrine are not very specific. Isoform-specific PKC inhibitors such as ruboxistaurin have been tested in clinical trials. Target-delivery of PKC pseudosubstrate inhibitory peptides and PKC siRNA may be useful in localized vascular disease. Further studies of PKC and its role in VSM should help design isoform-specific PKC modulators that are experimentally potent and clinically safe to target PKC in vascular disease.